APLICACIÓN DE HERRAMIENTAS Y TÉCNICAS DE ANÁLISIS FINANCIERO PARA LA CONSTRUCTORA BERLEVAQ CÍA. LTDA. DE LA CIUDAD DE LOJA EN EL PERÍODO 2013-2015 - Zhapa Peralta, Rosa Elizabeth (2018)
The present investigation is titled, “APPLICATION OF TOOLS AND FINANCIAL ANALYSIS TECHNIQUES FOR THE CONSTRUCTOR BERLEVAQ CÍA. LTDA OF THE CITY OF LOJA IN THE 2013-2015 PERIOD”, for this purpose the general objective was to carry out an analysis of the financial situation through the application of tools and techniques of financial analysis that allow evaluating the situation and performance of the finances of the construction, and as specific objectives, make a diagnosis of the current situation of the same; know the structure and financial variations; identify their weak points; and finally develop improvement strategies based on the results obtained. For the development of these objectives, a methodology applied to companies in this sector was used, which consists of the basics for the realization of vertical analysis, horizontal analysis, DuPont system, EVA, as well as for financial indicators. The appropriate financial structure is presented, since it is represented for the most part by shareholders' own capital and in a minimum by the obligations with third parties. It is also observed that the company during the three years of analysis has varied with decreases and increases in its assets and liabilities, and a sustained increase in its equity, given specifically for its usefulness. In the application of the indicators, it was determined that the company does not have a high level of indebtedness in relation to assets and assets, something good for the construction company; and a liquidity that meets the recommended standards. Thus, it is concluded that the construction company has an adequate financial structure according to its economic activity, and recommending maintaining it in order to avoid indebtedness of it, and take more advantage of its resources to increase its performance.